Postharvest development of lilies (Lilium sp.), produced in Duitama-Boyacá and a flower cut point determination (2013)
Colombia offers a large exportation of cut flowers, one of these is known as Asian lilies (Lilium spp.). This specie began to be grown in Boyacá in 2000, obtaining an excellent flower quality in terms of size, strength, colour, and vase life. Then, some problems were shown with the vase life. This aspect made it more evident when warm weather was the final destination. Therefore, it was necessary a postharvest cut points determination, selection methods and classification criteria used by Duitamenses producers Tests were conducted in Duitama at La Argentina farm with Nello (red) and Girondo (pale yellow) flowers varieties. Testings were developed at UPTC postharvest laboratory, taking 5 floral apertures stages by variety, with 3 stems and 5 replications. Finally, the best cut point and the optimal floral aperture stage were obtained.